2015
DOI: 10.1371/journal.pone.0113816
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Analysis and Chromosomal Characteristics of the Polymorphic 18S rDNA of Haliotis discus hannai from Fujian, China

Abstract: We report on novel chromosomal characteristics of Haliotis discus hannai from a breeding population at Fujian, China. The karyotypes of H. discus hannai we obtained from an abalone farm include a common type 2n = 36 = 10M + 8SM (82%) and two rare types 2n = 36 = 11M + 7SM (14%) and 2n = 36 = 10M + 7SM + 1ST (4%). The results of silver staining showed that the NORs of H. discus hannai were usually located terminally on the long arms of chromosome pairs 14 and 17, NORs were also sometimes located terminally on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 29 publications
3
13
1
Order By: Relevance
“…However, in the present study, the A. fangsiao karyotype (32SM+16SM+12T) had twelve telocentric chromosomes, which disagrees with Gao and Natsukari 1990 (32M+28SM) and Adachi et al 2014 (48M+8M/SM+4SM), who contend that this species has only M and SM chromosomes. Furthermore, the karyotype formula we found for this species was different from previous reports, which may be due to differences in sampling and preparation methods causing chromosome polymorphism, which is common in shellfish (Wang et al 2015a). Arslan and Zima (2015) also emphasized that a cytotype may include several populations with different karyotypes despite having the same diploid number of chromosomes.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, in the present study, the A. fangsiao karyotype (32SM+16SM+12T) had twelve telocentric chromosomes, which disagrees with Gao and Natsukari 1990 (32M+28SM) and Adachi et al 2014 (48M+8M/SM+4SM), who contend that this species has only M and SM chromosomes. Furthermore, the karyotype formula we found for this species was different from previous reports, which may be due to differences in sampling and preparation methods causing chromosome polymorphism, which is common in shellfish (Wang et al 2015a). Arslan and Zima (2015) also emphasized that a cytotype may include several populations with different karyotypes despite having the same diploid number of chromosomes.…”
Section: Discussioncontrasting
confidence: 99%
“…Microphotographs of the chromosomes were used for karyotype analysis with Image-Pro Plus 6.0 (Wang et al 2015a). Chromosomes were extracted from the original images, with homologous chromosome pairing and sorting based on visual observation.…”
Section: Methodsmentioning
confidence: 99%
“…According to the report of Okumura et al (1999), NORs of the Haliotisdiscushannai were located at the end of two pairs of chromosome long arms, and it was also found in the subcentral centromeric chromosome and the centromeric chromosome. Similarly, in the later studies of abalone chromosomes from Wang et al (2015) showed NOR sites located on the 14 th and 17 th chromosomes, but at the end of the short arms of central and submetacentric chromosomes also were found the sites. From the two studies, the same species proved that the polymorphism of Ag-NOR bands was prevalent among most species, including crustaceans, teleost fish, reptiles, mammals and other mollusks (Babu and Verma 1985, Thiriot-Quiévreux and Insua 1992, Vitturi and Lafargue 1992, Cross et al 2003, Britton-Davidian et al 2011).…”
Section: Discussionmentioning
confidence: 56%
“…O.minor and A.fangsiao had two NORs which located terminally on a pair of homologous chromosomes. As an effective chromosome marker, polymorphisms in NORs can be observed in interspecies or intraspecies comparisons, including the number, location and size of sliver staining (Wang et al 2015, Zaleśna et al 2017), even the geographical location and habitat differences can cause the diversity. However, many studies have determined that the number of NORs in interphase is consistent with that on metaphase plates of the same species (Iizuka et al 2013, Zaleśna et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Pacific abalone (Haliotis discus hannai) is one of the noticeable marine gastropods as a food source in eastern Asia (Wang et al, 2015). Thus, it has been subjected to a number of studies regarding an improvement of its productivity and quality through selective and genetic breeding technologies (Elliott., 2000).…”
Section: Introductionmentioning
confidence: 99%